Trimethylchlorosilane (TMCS) modified hydrophobic silica dry gel (TSA) enhanced the optical, aging behavior and thermal properties of polyvinyl butyral composite coatings - Enwen Liu; Yijuan Chang; Haiqiao Zhang; Zhangbei Chen; Zhihui Wu (Case Studies in Construction Materials)
In this study, hydrophobic silica dry gel (TSA) modified by trimethylchlorosilane (TMCS) was fabricated using liquid sodium silicate and hydrogen peroxide as raw materials through a green and efficient room-temperature drying approach. Subsequently, TSA was uniformly dispersed into a slurry by the aqueous solution of polyvinylpyrrolidone (PVP), which was then distributed into polyvinyl butyral resin (PVB) for the fabrication of TSA/PVP-PVB composite coating. The optical properties, mechanical properties, aging resistance, and heat and insulation properties of the composite coating were regulated by controlling the amount of TSA paste. The experimental results demonstrate that the introduction of TSA enhances the optical properties of the composite coating: The solar reflectance reaches up to more than 50 %, the transmittance of composite coatings within 15 % TSA is higher than 60 % and the haze is higher than 95 %, thereby improving the anti-ultraviolet aging performance (after 120 h aging treatment, its color difference, gloss, water contact angle (WCA) and microstructure remain stable). The tensile strength and fracture strain decreased as the addition amount increased. Meanwhile, the WCA rose from 42.7° (pure PVB) to 95.4° (30 % TSA composite coating). Interestingly, when we placed the 1 mm thick 30 % TSA composite coating on the heating plate for 10 s at 100 ℃, the surface temperature was only approximately 52.5 ℃, and the heat insulation efficiency was close to 50 %. Additionally, the thermal conductivity of the pure PVB coating was 0.211 W/(m·K), and the TSA content was inversely proportional to the thermal conductivity. The thermal conductivity of the 30 % TSA composite coating was reduced to 0.068 W/(m·K). Compared with traditional methods, the composite coating prepared in this study is more environmentally friendly, economical, and energy-saving, and has outstanding building protection performance.